(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we consider the Cauchy problem of the 3D generalized MHD system with nonlinear damping terms. We establish the global existence of strong solutions with the help of damping terms. Furthermore, we consider the balance between damping terms.